Large Language Models Limitations in Representing Filipino Transgender and Non-Binary Identities and the Use of Swardspeak: A Meta-Synthesis Framework - Nafiseh Zarei; Ramon Oliver Garcia (Saree: Research in Gender Studies, 2026)
Large Language Models (LLMs) are rapidly being integrated into society. However, questions remain about their safety and appropriateness for minorities like the Lesbian, Gay, Bisexual, Transgender, and Queer (LGBTQ), especially for non-Western Transgender and Non-Binary (TGNB) individuals. Therefore, this study reviews research on the interaction of LLMs with LGBTQ and TGNB people, LGBTQ linguistic phenomena, and the linguistic phenomena of Filipino LGBTQ people. A qualitative systematic review was conducted on 36 studies published from 2019 to 2026. Using thematic analysis, harmful patterns of LLMs were discovered, such as the propagation of LGBTQ stereotypes, misgendering, and a lack of context and sensitivity to the TGNB experience. In the Filipino context, there are also problems due to the lack of TGNB terminology and local stereotypes. The study, therefore, proposes a conceptual framework based on Intersectionality to examine the overlapping biases that affect TGNB Filipinos LLM users. Using critical analysis, the study contributes to discussions for equitable and culturally sensitive LLMs, as well as research on minority language communities and non-Western contexts. Abstract TagalogAng mga Large Language Models (LLM) ay mabilis na ininintegra sa lipunan, pero may nanatiling kweston tungkol kung ligtas at angkop ito para sa mga minoridad na Lesbian, Gay, Bisexual, Transgender, at Queer (LGBTQ), espesyal ang mga hindi-Kanluranin na Transgender at Non-binary (TGNB). Kaya ang pag-aaral na ito ay sinisuri ang mga pananaliksik tungkol sa interaksyon ng mga LLM sa mga LGBTQ at TGNB, mga penomenong lingguwistika ng LGBTQ, at ang penomenong lingwistika ng Pilipino LGBTQ. Kwalitatibong sistematikong pagsusuri ang isinagawa sa 36 na pag-aaral na inilathala noong 2019 hanggat 2026. Gamit ang tematikong pagsusuri, na diskubre ang mga mapaminsalang pattern ng LLM tulad ng pagparami ng mga LGBTQ stereotype, at pag-misgender, at kakulangan ng kontekso at sensitibo sa karanasang TGNB. Sa Pilipinong konteksto, may mga problema din dahil sa kakulangan ng terminong pang TGNB at mga lokal na stereotype. Kaya nagmumungkahi ang pagaaral ng konseptwal na balangkas batay sa Interseksyonalidad, para suriin ang magkasanib na bias na umaapekto sa mga TGNB Pilipinong gumagamit ng mga LLM. Gamit ang pagsusuring kritikal, umaambag ang pag-aaral sa mga talakayan para sa patas at sensitibo-sa-kultura ng mga LLM, an mga subjke sa pananaliksik tungkol sa minoryang komunidad ng wika at mga hindi-Kanluranin kontekstong.